2016
DOI: 10.3171/2015.1.jns141571
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical abnormalities in the absence of acute deficits in mild primary blast-induced head trauma

Abstract: OBJECTIVE Blast-induced neurotrauma (BINT), if not fatal, is nonetheless potentially crippling. It can produce a wide array of acute symptoms in moderate-to-severe exposures, but mild BINT (mBINT) is characterized by the distinct absence of acute clinical abnormalities. The lack of observable indications for mBINT is particularly alarming, as these injuries have been linked to severe long-term psychiatric and degenerative neurological dysfunction. Although the long-term sequelae of BINT are extensively documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 76 publications
(173 reference statements)
5
71
0
Order By: Relevance
“…; Walls et al . ), but also degenerative diseases, such as multiple sclerosis and Alzheimer's disease (Calingasan et al . ; Leung et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Walls et al . ), but also degenerative diseases, such as multiple sclerosis and Alzheimer's disease (Calingasan et al . ; Leung et al .…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, acrolein likely damages the lipid membrane through direct destruction of membrane-bound proteins, as well as through lipid peroxidation by ROS. It has been suggested that acrolein plays a pathological role in not only neuronal trauma, such as SCI and traumatic brain injury (Luo et al 2005b;Hamann et al 2008a;Walls et al 2016), but also degenerative diseases, such as multiple sclerosis and Alzheimer's disease (Calingasan et al 1999;Leung et al 2011), cancers (Cohen et al 1992;Feng et al 2006), and chemotherapy-induced neuropathy (Conklin 2004;Barrera 2012). Therefore, removing acrolein by acrolein scavengers Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additional forms of analysis could employ a multiple protein target analysis using a multiplex ELISA method or protein array chips (Buttram et al, 2007; Mukherjee et al, 2011; Gyorgy et al, 2010; Kovesdi et al, 2012). For a yet larger scale detection of proteins changed by TBI, one could employ a mass spectrometry analysis approach (Ding et al, 2015; Sheth et al, 2015; Walls et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…2 Although the physiological consequences of brain deformation; that is, tertiary injury, are well studied, 3,4 the pathobiology of TBI caused by primary blast, or shock-wave exposure, remains debated. 5 Animal studies that investigated the effects of primary blast injury have produced conflicting results for motor [6][7][8][9][10][11] and cognitive deficits. 8,9,12,13 One potential reason for these discrepancies is the lack of standardization in several critical factors in the bTBI injury models, such as verification of head immobilization, thoracic protection, blast exposure magnitude and duration, and subject orientation.…”
Section: Introductionmentioning
confidence: 99%